GAMBARAN KUALITAS HIDUP PASIEN DIABETES MELLITUS DI PUSKESMAS PEKAUMAN BANJARMASIN - Eri Setiani; Cynthia Eka Fayuning Tjomiadi; Onieqie Ayu Dhea Manto (STIKES Suaka Insan, 2024)
Diabetes Mellitus is a disorder of carbohydrate, protein and fat metabolism characterized by hyperglycemia. Hyperglycemia can occur due to decreased insulin action. Diabetes Mellitus sufferers experience changes and imbalances in various aspects of their lives that interfere with daily activities, this condition can reduce the sufferer's quality of life. Pekauman Health Center Banjarmasin is the health center with the most cases of diabetes mellitus in Banjarmasin city with an increase from 111 patients in December 2023 to 137 patients in January 2024. This study aims to describe the quality of life of Diabetes Mellitus patients at the Pekauman Banjarmasin Community Health Center. This quantitative research with a descriptive analytical design was carried out on 48 patients suffering from Diabetes Mellitus who were selected using a purposive sampling technique using the EQ5D-5L questionnaire which was analyzed univariately. The majority of respondents were adults (72.9%), women (62.5%), had a BMI of Obesity I (37.5%), and suffered from Diabetes Mellitus ?1 year (60.4%). The quality of life of most Diabetes Mellitus sufferers is in the poor category (56.3%). The quality of life of Diabetes Mellitus patients is included in the poor category with the dominant symptom being anxiety. The poor quality of life in Diabetes Mellitus sufferers is related to the characteristics of the majority of respondents being women aged >50 years who have a BMI category of Obesity I and have suffered from DM for ?1 year. Keywords: Characteristics, Diabetes Mellitus, Quality of Life.